A PVdF-based electrolyte membrane for a carbon counter electrode in dye-sensitized solar cells. Issue 34 (12th April 2017) - Sun, Kyung Chul; Arbab, Alvira Ayoub; Sahito, Iftikhar Ali; Qadir, Muhammad Bilal; Choi, Bum Jin; Kwon, Soon Chul; Yeo, Sang Young; Yi, Sung Chul; Jeong, Sung Hoon
Abstract : This research demonstrates the design and operation of a dye-sensitized solar cell (DSSC) with a multi-walled carbon nanotube counter electrode (CE) and a pore-filled membrane consisting of polyvinylidene fluoride- co -hexafluoropropylene (PVdF- co -HFP) as an electrolyte. Abstract : This research demonstrates the design and operation of a dye-sensitized solar cell (DSSC) with a multi-walled carbon nanotube counter electrode (CE) and a pore-filled membrane consisting of polyvinylidene fluoride- co -hexafluoropropylene (PVdF- co -HFP) as an electrolyte. In this cell, the internal resistance was substantially reduced and the efficiency was found to be as high as 6.04% under 1 sun. For this purpose, a sequence of experiments was carried out to demonstrate that the PVdF- co -HFP membrane possessed superior porosity to absorbed electrolytes and is more compatible with MWCNT CE as compared to the commonly used liquid electrolyte. For a comparison of results, different types of DSSC assemblies composed of MWCNT CEs were fabricated with liquid-, gel- and electrolyte-filled PVdF- co -HFP membranes. Morphological studies showed that the PVdF- co -HFP membrane is a regular and highly porous nano-web which provides optimized interfacial contact with defect-rich MWCNT CE. Detachment of the carbon particles from the CE causes short circuits and lower efficiency of the DSSCs. The proposed DSSC design not only lowers the interfacial charge transfer resistance ( R CT = 2.98 Ω) but also reduces the risk of short circuits in the cell. This sustainable and highly efficient DSSC structure provides a new method for the simple fabrication of flexible solar cells and electronic devices.